Purkinje-cell-specific DNA repair-deficient mice reveal that dietary restriction protects neurons by cell-intrinsic preservation of genomic health - Birkisdóttir, María Björk; Van’t Sant, Lisanne J.; Brandt, Renata M. C.; Barnhoorn, Sander; Hoeijmakers, Jan H. J.; Vermeij, Wilbert P.; Jaarsma, Dick (Frontiers in Aging Neuroscience, 2023)
Dietary restriction (DR) is a universal anti-aging intervention, which reduces age-related nervous system pathologies and neurological decline. The degree to which the neuroprotective effect of DR operates by attenuating cell intrinsic degradative processes rather than influencing non-cell autonomous factors such as glial and vascular health or systemic inflammatory status is incompletely understood. Following up on our finding that DR has a remarkably large beneficial effect on nervous system pathology in whole-body DNA repair-deficient progeroid mice, we show here that DR also exerts strong neuroprotection in mouse models in which a single neuronal cell type, i.e., cerebellar Purkinje cells, experience genotoxic stress and consequent premature aging-like dysfunction. Purkinje cell specific hypomorphic and knock-out ERCC1 mice on DR retained 40 and 25% more neurons, respectively, with equal protection against P53 activation, and alike results from whole-body ERCC1-deficient mice. Our findings show that DR strongly reduces Purkinje cell death in our Purkinje cell-specific accelerated aging mouse model, indicating that DR protects Purkinje cells from intrinsic DNA-damage-driven neurodegeneration.